Dimensi Pengalaman Spiritual dalam Praktik Zikir Tarekat Qadiriyah wa Naqsyabandiyah - Arju Mushaffa; Muhammad Arifin; Muhammad Ulul Azmi; Imam Junaris (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to describe the dimensions of the spiritual experiences of the congregants of the Qadiriyah wa Naqsyabandiyah Tarekat under the guidance of Ulul Albab at the Integrated Islamic Boarding School Daru Ulil Albab, Nganjuk, as well as to analyze the influence of teachings and the practice of dhikr on changes in congregants' behavior. The approach used is qualitative with a phenomenological research type, conducted through observation, in-depth interviews, and document analysis. Data analysis is carried out through data reduction, data presentation, and verification using source triangulation. The research findings indicate that the spiritual experiences of the followers of the Qadiriyah wa Naqsyabandiyah Order are reflected in five main aspects: self-transformation, inner peace, awareness of always remembering Allah, consistency in worship, and the ability to maintain a balance between spirituality and worldly life. The practice of dhikr, especially dhikr nafi isbat and ismu zat, serves as the main means that fosters tranquility, enhances self-control, and strengthens discipline in worship. These findings align with William James' theory of spiritual experience, particularly regarding the noetic, ineffability, transiency, and passivity aspects, and are relevant to Max Weber's theory of social action, which shows that the behavior of the followers is influenced by a combination of value-rationality and instrumental rationality. This study affirms that the practices of the Qadiriyah wa Naqsyabandiyah Order play an important role in shaping the spiritual depth and behavioral changes of its followers.   Keywords: Spiritual Experience, Sufi Order, Qadiriyah and Naqshbandiyah, Dhikr, Social Action